2015
DOI: 10.1007/s00417-015-3031-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experience after intravitreal ocriplasmin for vitreomacular traction and macular hole: a spectral-domain optical coherence tomography prospective study

Abstract: Our study demonstrated a VMT release rate of 66.7 %. Apart from the known baseline factors that influence VMT release after ocriplasmin injection, the size of the vitreofoveal angle, a V-shaped and loose vitreomacular adhesion, a small adhesion area, and thin vitreous strands at the adhesion site, could additionally affect the outcome of VMT release. In addition, we studied when VMT release and concomitant events occur and for how long the induced complications lasted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
5
24
0
1
Order By: Relevance
“…1,36 Ocriplasmin is a recombinant truncated form of human plasmin that has proteolytic activity against fibronectin, laminin and collagen, which are present at the vitreoretinal interface and help anchor the vitreous cortex to the retina. 39 Ocriplasmin was approved by the US Food and Drug Administration (FDA) in 2012 after safety and efficacy were established in two phase III clinical trials (MIVI-TRUST 006/007, NCT00781859 and NCT00798317, respectively) involving 652 patients with symptomatic VMA.…”
Section: Ocriplasmin Overview and Review Of Recent Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,36 Ocriplasmin is a recombinant truncated form of human plasmin that has proteolytic activity against fibronectin, laminin and collagen, which are present at the vitreoretinal interface and help anchor the vitreous cortex to the retina. 39 Ocriplasmin was approved by the US Food and Drug Administration (FDA) in 2012 after safety and efficacy were established in two phase III clinical trials (MIVI-TRUST 006/007, NCT00781859 and NCT00798317, respectively) involving 652 patients with symptomatic VMA.…”
Section: Ocriplasmin Overview and Review Of Recent Publicationsmentioning
confidence: 99%
“…Three of 18 studies reported VA improvement in a subset of patients; two studies showed VA improvement in patients who achieved VMA/ VMT release, 1,60 and one study showed patient VA improvement following FTMH closure, but not for patients without FTMH closure. 15 cases with analysable VA data.…”
Section: Ocriplasmin Overview and Review Of Recent Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, following the MIVI-TRUST trials, several authors described some small series (10-58 eyes) from the real clinical setting with higher resolution rates after ocriplasmin injection, ranging from 30 to 71% [7,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Still, real-life experience data is limited and usually from single-center retrospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to define the best candidates with a more favourable response to ocriplasmin: traction with a focal vitreomacular adhesion (<1500 μm), the absence of any epiretinal membrane (ERM), in cases of macular holes showing traction limited to a smaller area (≤250 μm), the presence of subretinal fluid, and younger age [6,7]. Incidentally, most of these factors also seem to increase the spontaneous resolution rate [5,6,8]. 2.…”
mentioning
confidence: 99%